Comparison of Generic (Rolexan) and Brand (Clexan) Forms of Enoxaparin in Critically Ill Patients: A Cross Over, Open Label, Randomized Prospective Clinical Trial - Shadi Ziaie; Hanieh Malekmohammadi; Mohammad Sistanizad (Research Center for Rational Use of Drugs (RCRUD), 2020)
Backgrounds: Several generic forms of enoxaparin were introduced to the market after expiring the patent of Clexane. But the main problem with generic forms is its bio-equivalency with brand form as a little difference in active ingredients characteristics, could led to significant clinical differences. For evaluating the efficacy of enoxaparin, it is recommended to measure its activity against Anti Xa. The aim of this study was comparison of Anti Xa Activity of Enoxan® versus Clexane ® in critically ill patients with prophylactic doses. Methods: This was a cross over, open label, randomized prospective study which was performed between September 2016 and December 2017 in intensive care unit of Labbafinezhad hospital, Tehran, Iran. Thirty adult patients, who received enoxaparin for prophylaxis of thromboembolic events, were recruited. Subjects were subsequently randomized to one of the treatment sequences (Generic-brand or brand-generic). The generic drug was enoxaparin sodium 40 mg (4,000 IU anti-FXa/0.4 mL), manufactured by Ronakpharm, Iran; the brand drug was enoxaparin sodium 40 mg (Clexane® 4,000 IU anti-FXa/0.4 mL), manufactured by Sanofi, France. Results: Anti-Xa activity was assessed with Stago kit. The anti-Xa activity between 0.2 and 0.5 U/mL was defined as prophylaxis. The average Anti-Xa activities of Clexan and Rolexan were 0.3±0.12 and 0.22±0.10, respectively which reveals statistically no significant difference (P: 0.35). Also Anti-Xa activity in 6 and 11 patients in Clexan and Rolexan groups were under 0.2 (P: 0.16). Conclusion: Our study showed comparable efficacy of prophylactic doses between Clexan and Rolexan in critically ill patients. Further studies in different patient population are recommended.